Blood pressure and glycemia levels of Family Health Strategy users - Niciane Bandeira Pessoa Marinho; Hérica Cristina Alves de Vasconcelos; Maria Amélia de Souza; Roberto Wagner Júnior Freire de Freitas; Paulo César de Almeida; Marta Maria Coelho Damasceno (Universidade Federal de Goias, 2014)
A quantitative study with the objective to identify the profile of blood pressure and glycemic levels of Family Health Strategy users in Itapipoca, state of Ceará, Brazil. We included 419 users, which provided us with sociodemographic and clinical data (capillary glycemia and systemic blood pressure). Participants ranged from 20 to 59 years; 88.1% were women; 8.3% had glycemia > 140mg/dl; 7.4% were pre-hypertensive and 5.2%, hypertensive. The prevalence of high blood pressure was greater among men (p< 0.001); in those between 45 and 59 years (p=0.003) and who were not single (p=0.002). Age and education level variables were directly and inversely related, respectively, to greater prevalence of high blood glucose and pressure levels. In conclusion, the studied population needs strategies for increasing participation in health promotion actions so as to minimize the rates of morbimortality related to altered blood pressure and glycemia levels that do not receive early detection. doi: 10.5216/ree.v16i3.22021.